Antimony-Doped Tin Oxide Nanocrystals for Enhanced Photothermal Theragnosis Therapy of Cancers - Lv, Zhongjing; Li, Jiafeng; Yang, Feng; Cao, Kun; Bao, Qiang; Sun, Yuhua; Yuan, Jian (Frontiers in Bioengineering and Biotechnology, 2020)
The doped semiconductor nanocrystal with free holes in valence band exhibits strong near-infrared (NIR) local surface plasmon resonance effects, which is essential for photothermal agents. Herein, the hydrophilic Sb doped SnO2 nanocrystals were successfully prepared by a simple hydrothermal synthesis method. The doping makes the Sb doped SnO2 nanocrystals possessing defect structures. Compared with the un-doped SnO2 nanocrystals, Sb doped SnO2 nanocrystals exhibit stronger absorption in the NIR region from 500 nm to 1100 nm and higher photothermal conversion efficiency (up to 73.6%) which make the synthesized Sb doped SnO2 nanocrystals be used as excellent photothermal agents. Importantly, Sb doped SnO2 nanocrystals can efficiently kill cancer cells both in vitro and in vivo under the irradiation of a 980 nm laser with a power density of 0.6 W cm-2.In addition, Sb doped SnO2 nanocrystals can also be served as efficient CT imaging agents owing to the large X-ray attenuation coefficient of tin.